2014
DOI: 10.1007/s10943-014-9821-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Holy Quran Voice on Mental Health

Abstract: This study was designed to determine the effect of Quran listening without its musical tone (Tartil) on the mental health of personnel in Zahedan University of Medical Sciences, southeast of Iran. The results showed significant differences between the test and control groups in their mean mental health scores after Quran listening (P = 0.037). No significant gender differences in the test group before and after intervention were found (P = 0.806). These results suggest that Quran listening could be recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 6 publications
5
39
0
11
Order By: Relevance
“…Results of different studies also show that there is a significant relationship between spiritual understanding and mental health. [16,25,26] Researches on "the effects of spirituality on health" have shown that spirituality is associated with lower amount of diseases and greater longevity. [27,28] When faced with an injury, people who have spiritual orientations respond better to treatments and better cope with injuries and defects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of different studies also show that there is a significant relationship between spiritual understanding and mental health. [16,25,26] Researches on "the effects of spirituality on health" have shown that spirituality is associated with lower amount of diseases and greater longevity. [27,28] When faced with an injury, people who have spiritual orientations respond better to treatments and better cope with injuries and defects.…”
Section: Discussionmentioning
confidence: 99%
“…According to same study, [16] 80 medical staff of Mazandaran University of medical sciences (Mazandaran, Iran) were gathered randomly according to inclusion criteria's. Inclusion criteria's were (i) complete satisfaction to study, (ii) absence of acute and chronic physical and mental illnesses (examined by the group's psychologist).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alquran adalah suatu jenis musik spritual (Khatoni, 1997). Mendengarkan Alquran dapat meningkatkan kesehatan jiwa dan membawa ketenangan (Mahjoob, Nejati, & Hosseini, 2016…”
Section: Latar Belakangunclassified
“…In the past, several studies have investigated the effect of listening to the Quran on performance and mental activity (14)(15)(16)(17). Also, a very limited number of other studies have examined the medical issues raised in the Quran, including medical plant (18), embryonic development in humans (19), heart and cardiovascular system (20), and treatment of various diseases (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%